2021
DOI: 10.1542/hpeds.2021-006045
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pediatric Faculty Burnout During the COVID-19 Pandemic

Abstract: OBJECTIVES To examine the impact of the coronavirus disease 2019 (COVID-19) pandemic and associated workflow changes, such as deployment on pediatric faculty burnout in an early epicenter of the pandemic. We hypothesized burnout would increase during the COVID-19 surge. METHODS We conducted serial cross-sectional surveys of pediatric faculty at an academic, tertiary-care children’s hospital that experienced a COVID-19 surge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…However, results are suggestive of important trends among working parents during the COVID-19 pandemic that have been documented in other professions (7,23,30). Additionally, although the demographics of the survey respondents and the faculty population were reportedly similar, the findings may be influenced by selfselection bias (13). We did identify that parents in their 40s experienced the highest levels of DWC, which may reflect having younger aged children, but the small sample size limited our ability to test an age-moderated model and the lack of data on child age made it impossible to explore this post hoc hypothesis.…”
Section: Finding Relief In Flexible Work Arrangementsmentioning
confidence: 59%
See 2 more Smart Citations
“…However, results are suggestive of important trends among working parents during the COVID-19 pandemic that have been documented in other professions (7,23,30). Additionally, although the demographics of the survey respondents and the faculty population were reportedly similar, the findings may be influenced by selfselection bias (13). We did identify that parents in their 40s experienced the highest levels of DWC, which may reflect having younger aged children, but the small sample size limited our ability to test an age-moderated model and the lack of data on child age made it impossible to explore this post hoc hypothesis.…”
Section: Finding Relief In Flexible Work Arrangementsmentioning
confidence: 59%
“…The parent study was designed as a faculty engagement survey that examined work-life domains, faculty burnout, demographic and work profile data. Detailed study design, recruitment methods and measures of the parent study are reported elsewhere (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although doodling was not found to be a potential measure of burnout under the restrictions imposed by COVID-19 for this particular group, measures of burnout have been developed and studied by psychometric researchers with respect to COVID-19 in various settings. Examples of these include: the COVID-19 Burnout Scale (COVID-19-BS) —investigating the mediating effect of resilience on the relationship between COVID-19 stress and burnout [ 36 ]; the Copenhagen Burnout Inventory—measuring burnout, as well as depression, anxiety, distress, and stress [ 37 ]; and the Maslach Burnout Inventory-Human Services Survey (MBI-HSS)—assessing burnout directly while highlighting emotional exhaustion [ 38 ]. Nevertheless, none of these measures employed and examined during COVID-19 were tested on researchers per se, nor are they simple to administer, as doodling might be if it were found useful as a measure.…”
Section: Discussionmentioning
confidence: 99%
“… 16 These deleterious effects are likewise felt by psychiatry practitioners who, although trained in the arena of mental health, are now tasked with seeing unprecedented volumes of pediatric patients in the inpatient setting due to the impact of COVID. 16 , 17 …”
mentioning
confidence: 99%